ANALYSIS OF THE APPLICATION OF POWERPOINT BASED VIDEO TO IMPROVE TEACHER ABILITY - Rina Marlina; Yeni Erita (STKIP Subang, 2022)
This research is motivated by the low ability of teachers in making learning media that can influence school quality. Varied and innovative learning media basically aim to create learning conditions that enable students to learn actively and have fun so they can achieve better learning outcomes and achievements. optimal. The purpose of this study was to describe the teacher's ability to make learning media using video-based Ms PowerPoint applications for teachers who are members of KKG SD Banuhampu District, Kab. Agam, through workshop activities. This type of research is qualitative, with a total population of 25 people. Data collection techniques in this study using the questionnaire method. The results showed that by implementing media-making workshops, the teacher's ability to create and use video learning media based on the Ms PowerPoint application could be improved